Revolutionizing Geography Education: Developing Mobile Learning Multimedia via the Nearpod Platform - Aditya Ramadhan (Future Space: Studies in Geo-Education, 2024)
Advancements in technology have significantly enriched the learning experience by addressing challenges associated with limited educational facilities. Multimedia in mobile learning has emerged as a pivotal technological adaptation, serving as an effective medium for content delivery. This research employs the initial stages of the ADDIE model, specifically the 'ADD' phases, to guide the development of the multimedia. These stages encompass a comprehensive needs analysis, intricate product design, subsequent development, rigorous validation, and a thorough feasibility evaluation. The culmination of this study presents a multimedia learning tool tailored for mobile learning on the Nearpod platform. This tool, seamlessly compatible with Android and iOS operating systems, incorporates visual aids such as images and videos, pertinent examples, interactive quizzes, and more. Upon evaluation, the multimedia received a media validation score of 96.66%, material validation of 98.33%, linguistic validation of 84.37%, and an overall student response rate of 86%.